Soft Annealing Technology of High Chromium White Cast Iron for Machinability - Nguyen, Ngoc Minh (Old Journal, 2019)
The objective of the present work is to establish the heat treating parameters necessary to impose high chromium white cast iron a lower range of hardness, acceptable to guarantee a reasonable machinability of the material. Samples are soft annealing under different conditions by a resistor furnace. Evaluation of the phase transformations during soft annealing was carried out by using optical microscopy (OM), scanning electron microscopy (SEM), X-ray diffraction (XRD) and microhardness tester. The results of this study have shown that soft annealing of high chromium white cast iron can be done by controlling the distribution of secondary chromium carbide on ferrite matrix.